Characterization of medication use among the elderly of North Portugal - Pinto, Isabel C. (2018)
Aging associated with chronic comorbidities leads to Polypharmacy, but the complex therapies in elderly can lead to therapy non-adherence, increasing costs and several health risks. Objectives: To characterize medication use and related factors among northern Portuguese elderly. Methods: This cross-sectional population-based study was centered on a structured interview to 442 elderly (≥65 years), non-probabilistic sample by convenience, at home and institutions in northern Portugal. It was considered as polymedicated seniors taking ≥5 drugs daily. Beers criteria (2012) were used to evaluate the potentially inappropriate medication use. It was used descriptive statistics and univariate and multivariate statistical analysis, with a significance level of 5%. Results: The sample consisted mainly of females (56.6%), aged between 65 and 101 years (mean 76.84 ± 8.07). The prevalence of medication use was 97.3%. Most elderly are polymedicated (54.1%), on average 5.15 different drugs are administered per day. The most commonly prescribed groups were: cardiovascular drugs (82.8%), central nervous system agents (54.2%) and drugs with an effect on the digestive tract (40.9%). According to the Beers criteria, 53.5% of seniors taking potentially inappropriate medication. Polypharmacy was positively associated with living in littoral sub-region (p<0.001), having a reasonable (p=0.002) or poor health self-perception (p<0.001), self-reported chronic diseases (p<0.001) and number of doctors (p=0.003). Conclusions: Results shows a high proportion of medication use among the northern Portuguese elderly, including potentially inappropriate. The risk of polypharmacy is related to coastal region, perception of reasonably/poor health, chronic diseases and the number of doctors.